2018
DOI: 10.22158/se.v3n4p329
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced PEMS Performance and Regulatory Compliance through Machine Learning

Abstract: <p><em>Modeling technologies</em><em> can pro</em><em>vide strong support to existing emission management systems, by means of what is known as a Predictive Emission Monitoring System (PEMS). These systems do not measure emissions through any hardware device, but use computer models to predict emission concentrations on the ground of process data (e.g., fuel flow, load) and ambient parameters (e.g., air temperature, relative humidity). They actually represent a relevant appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…PEMS, which is the device used in the study presented in this paper, was designed to provide an alternative to the drawbacks of the CEMS [29]. Built upon the findings of their first study, Si et al incorporated gradient boosting techniques in subsequent research to improve their results [30]. Other researchers have shown that the combination of NN and heuristic algorithms would further enhance the results [14].…”
Section: On-road Vehiclesmentioning
confidence: 99%
“…PEMS, which is the device used in the study presented in this paper, was designed to provide an alternative to the drawbacks of the CEMS [29]. Built upon the findings of their first study, Si et al incorporated gradient boosting techniques in subsequent research to improve their results [30]. Other researchers have shown that the combination of NN and heuristic algorithms would further enhance the results [14].…”
Section: On-road Vehiclesmentioning
confidence: 99%